Reason 3 Power! - Piper, Matt (Course Technology PTR, 2008)
Geared toward intermediate users, "Reason 3 Power!" is a perfect book for the home recording studio musician! Readers learn how to use Reason with other software and hardware through in-depth tutorials and explanations. This guide is packed with tips that even a quite experienced user may not be aware of. It provides the "why" behind the "how" so readers leave this book with a better overall knowledge of the ins and outs of the application. The authors cover Reason from A to Z in order to bring readers up to "power user" status. This book explores the history of MIDI, how Reason works with MIDI, and valuable tricks of the trade that will help make readers' songs sound professional. Whether it's for a professional musician or a hobbyist, "Reason 3 Power!" coupled with this dynamic software will take the creative possibilities to a whole new level